The impact of hearing impairment and hearing aid use on progression to mild cognitive impairment in cognitively healthy adults: An observational cohort study - Magda Bucholc; Sarah Bauermeister; Daman Kaur; Paula L. McClean; Stephen Todd (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2022)
Abstract Introduction We assessed the association of self‐reported hearing impairment and hearing aid use with cognitive decline and progression to mild cognitive impairment (MCI). Methods We used a large referral‐based cohort of 4358 participants obtained from the National Alzheimer's Coordinating Center. The standard covariate‐adjusted Cox proportional hazards model, the marginal structural Cox model with inverse probability weighting, standardized Kaplan‐Meier curves, and linear mixed‐effects models were applied to test the hypotheses. Results Hearing impairment was associated with increased risk of MCI (standardized hazard ratio [HR] 2.58, 95% confidence interval [CI: 1.73 to 3.84], P = .004) and an accelerated rate of cognitive decline (P < .001). Hearing aid users were less likely to develop MCI than hearing‐impaired individuals who did not use a hearing aid (HR 0.47, 95% CI [0.29 to 0.74], P = .001). No difference in risk of MCI was observed between individuals with normal hearing and hearing‐impaired adults using hearing aids (HR 0.86, 95% CI [0.56 to 1.34], P = .51). Discussion Use of hearing aids may help mitigate cognitive decline associated with hearing loss.